SOSIALISASI PEMASARAN DIGITAL MELALUI SOSIAL MEDIA DAN LEGALITAS USAHA BAGI PELAKU UMKM DI DESA CIREUNGHAS - Euis Lisnawati (HARUPAT: Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
This community service program aims to improve the understanding of Micro, Small, and Medium Enterprises (MSMEs) in Cireunghas Village, Cireunghas District, Sukabumi Regency regarding the importance of business legality through ownership of a Business Identification Number (NIB) and the use of digital marketing strategies. This activity was carried out through a socialization session that discussed NIB and digital marketing. In this activity, participants received information about the importance of business legality and the benefits of having a NIB, such as ease in the licensing process and processing of legal documents through the Online Single Submission (OSS) system. Furthermore, the activity focused on providing education about digital marketing to help MSMEs expand their market reach through social media. Based on the evaluation results, the majority of business actors showed interest in registering a NIB and began to understand the essence of digital marketing. The mentoring process in registering a NIB went smoothly, with participants successfully obtaining NIB documents efficiently. It is hoped that this program can contribute to increasing the capacity and competitiveness of MSMEs in the region.